IDENTIFICATION OF MANGROVE FOREST DAMAGE, AND EFFORT TO CONSERVATION IN BALIKPAPAN CITY, EAST KALIMANTAN, INDONESIA - Yaskinul Anwar; Iya' Setyasih; Ardiansyah Ardiansyah; Dwi Partini; Ratih Puspita Dewi; Yunus Aris Wibowo (Universitas Sebelas Maret (UNS), 2021)
The rapid development of Balikpapan City has an impact on the increasingly high demand for land for urban expansion needs. The expansion of Balikpapan City is more directed towards coastal areas which are dominated by mangrove forests. This study discusses the destruction of the mangrove forest and its causal factors and how conservation efforts are being carried out to maintain sustainability. Mangrove forest damage data obtained through surveys and image analysis using NDVI. While the factors causing the damage to mangrove forests were obtained from observations and interviews with the mangrove center manager of Balikpapan. The results showed that there were many mangrove forests that had rare or already damaged that were spread in the West Balikpapan, North Balikpapan, and East Balikpapan Sub-district. This damage is caused by natural and non-natural factors. Natural factors that cause damage to mangrove forests are pests and sedimentation. The non-natural factors are due to the pollution and the opening of fish ponds. Preservation efforts are carried out by replanting mangroves which are only carried out by the mangrove center and some CSR and environmentalists and do not involve the community at large. These Conditions make the mangrove forest in Balikpapan City threatened its sustainability.